Environmental-economic efficiency of land use improvement reasoning - Опара, В. М.; Бузіна, І. М.; Винограденко, С. О. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2017)
Formulation of the problem. In the conditions of fast development of the industry, energetics and transport communications, intensive mining of minerals, active chemicalixation of agriculture there is a fast increase in the level of environmental pollution and first of all soils, that in turn leads to worsening in their qualitative state. The soil is an important unit of ecosystems, the destruction of which has multidimensional value for the stability of the environment. Agrarian transformation of soils traditionally was assessed as progressive. However, scientific analysis shows that extensive agriculture, irrational chemical fertilizer and excessive adding of pesticides led to a significant reduction in fertility, and sometimes loss due to erosion, natural soil cover on large areas. The purpose of the article. The study of intensification of land resources in compliance with environmental principles, which should provide a comprehensive, systematic approach to solving economic, social, environmental and other problems.Methods. The author s own achievements as well as the research results of domestic and foreign investigators made the methodical basis for the article.Results. Ecological agriculture nowadays scientists consider a perspective direction, which allows the use of science-based pesticides and fertilizers without reducing the quality of made production, with compulsory advancing ecologization of processing industry. The result of activation of economic activity in many cases is increasing influence on the environment, ecological balance, soil pollution, depletion of land resources, worsening their useful properties.According to parameters of the regression model, the increase in all investigated factors other than labor costs with deductions, rendered positive influence on the resultant figure. In our case, most (relative to other factors) contributed to his growth increasing costs of seeds and planting materialbecause each additional spent thousand for this trend intensifying per one hundred hectares of arable land (if not the variability of other factors) predetermined increase yield of gross output of one point eighteen thousand UAH on one hundred hectares of arable land.Parameters of the given model demonstrated that increase in all studied factors rendered positive impact on a productive indicator.Scientific novelty and practical significance. One of the main mechanism for regulating ecologisation of land resources is the detection, evaluation and implementation of the highest possible reserves of increase efficiency of this process. This is a reduction of unproductive losses in resource use and saving mode, and the possibility of using scientific and technological progress as the main solution. Using regression models, that were built before, depending on the main indicators of ecological and economic efficiency of using of land resources on the arable land from specific costs, were identified reserves of increase in the investigated agricultural enterprises.